Analysis of the Influence of the Implementation of Minimum Service Standards (SPM) of Hospitals on the Satisfaction of Inpatients at Drs. H. Amri Tambunan Lubuk Pakam Regional Hospital - okto hebron purba okto (Medistra Medical Journal (MMJ), 2025)
Hospital service quality standards are the most important factor in patient satisfaction. In Indonesia, the implementation of Minimum Service Standards (SPM) in hospitals aims to ensure equitable, safe, and quality health services. This study aims to analyze the effect of SPM implementation on inpatient satisfaction at Drs. H. Amri Tambunan Lubuk Pakam Regional Hospital. This study was conducted using a quantitative analytical approach with a cross sectional design. Data were collected using a questionnaire distributed to one hundred inpatients selected by purposive sampling. The analysis used the chi-square test and logistic regression. The results showed a significant relationship between the implementation of SPM indicators of punctuality, service procedures, responsiveness of officers, and availability of facilities and infrastructure with inpatient satisfaction. It can be concluded that the better the hospital implements SPM, the higher the level of inpatient satisfaction. Therefore, consistent implementation of SPM must be a strategic focus for improving service quality.